Maternal Obesity and Gestational Diabetes Mellitus: The Pathological Programming. - Hazrat, Hina; Ahmed , Sadaf (International Journal of Endorsing Health Science Research, 2017)
Background: Onset or development of glucose intolerance during the period of gestation is termed as gestational diabetes mellitus. Maternal obesity along with GDM is found associated with development of adverse maternal and fetal health outcomes. Method: Researches with a focus on maternal obesity and gestational diabetes mellitus were included in this study. Results: Elevated state of maternal body mass index is found to raise the inflammatory condition in GDM, which may play role in impacting downstream metabolic processes giving rise to manifestation of glucose dysregulation and condition of insulin resistance. Obesity in gestation, is related to the alterations in metabolic status comprising dyslipidemia, hyperinsulinemia, impaired endothelial functioning, and increased blood pressure. Conclusion: Previous studies have provided findings associating the risk of GDM development with the state of BMI, which emphasizes the need to explore mechanisms governing obesity mediated GDM development and related maternal and fetal health complications during gestation. In view of existing literature, weight management and engagement in physical activities should be encouraged among women during and after the period of gestation.